Improved Maturity and Ripeness Classifications of Magnifera Indica cv. Harumanis Mangoes through Sensor Fusion of an Electronic Nose and Acoustic Sensor - Ammar, Zakaria; Ali Yeon, Md Shakaff, Prof. Dr.; Maz Jamilah, Masnan; Fathinul Syahir, Ahmad Saad; Abdul Hamid, Adom, Prof. Dr.; Mohd Noor, Ahmad, Prof. Dr.; Mahmad Nor, Jaafar, Assoc. Prof. Dr.; Abu Hassan, Abdullah; Latifah Munirah, Kamarudin (MDPI AG, 2013)
Link to publisher’s homepage at http://www.mdpi.com